Study on genetic variations of the D-loop region in three Vietnamese ethnic groups Kinh, Lolo and Lahu - Duong, Nguyen Thuy; Van Phong, Nguyen; Thy Ngoc, Nguyen; Van Hai, Nong (Vietnam Journal of Biotechnology, 2020)
Mitochondrial DNA (mtDNA) sequence analysis has been widely used to investigate population genetic and evolutional history of different ethnic groups worldwide. In this study, the D-loop region of 119 Vietnamese individuals belonging to three different ethnic groups was sequenced and compared with reference mtDNA on rCRS for genetic variations. Total 218 genetic polymorphisms were found in this population, among which 48 variations appeared with frequencies of more than 0.1. Further statistical analysis showed that there were 23, 13 and 24 single nucleotide polymorphisms (SNP) distributed differently between Kinh vs. Lolo, Kinh  vs. Lahu , and Lolo  vs. Lahu groups, respectively. The mean pairwise genetic distances between each pair of ethnic groups were 0.0101, 0.0098 and 0.0092 for Kinh - Lolo, Kinh - Lahu, Lolo - Lahu, respectively. This indicated that although the Lolo and Lahu ethnic groups both belong to the Tibeto-Burman language group, the genetic distance between them was no closer than the genetic distances between them and the Kinh group of the Viet-Muong (Austroasiatic) language group. This study was the first research on the D-loop region of the Lolo and Lahu populations in Vietnam. These results provided more data for exploring the genetic background and the history of those ethnic groups as well as other minority ethnic groups in Vietnam.